Time-motion analysis of young competitive surfers: Southern Portugal - Minghelli, B.; Graça, S.; Paulino, S.; Sousa, I. (Journal of Sports Medicine & Doping Studies, 2017)
Introduction: Time-motion analysis should be an integral part of the coaching process in competitive surf to help design training programs, as well as maximize athlete performance. There are a few studies that analyzed the timemotion of surfer activities during competition. Thus, the aim of this study was evaluate each activity`s time made by surfers during the heat competition, in order to account for the time spent in each surf activity.